2014
DOI: 10.1007/s13197-014-1399-2
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid rich extract of Murraya Koenigii alleviates in-vitro LDL oxidation and oxidized LDL induced apoptosis in raw 264.7 Murine macrophage cells

Abstract: Several lines of evidences have established a lineage between Oxidised LDL (Ox-LDL) to apoptosis of macrophages in which the high level of intracellular cholesterol play a crucial role. This study assesses the potency of Murraya koenigii (MK) leaf extract in alleviating LDL oxidation and Ox-LDL induced lipotoxicity in murine macrophage (RAW 264.7) cells. Results indicated that presence of MK extract prevented oxidation of LDL as evidenced by its oxidation kinetics and formation of LDL oxidation products. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 41 publications
1
16
2
Order By: Relevance
“…Cytotoxicity (MTT) assay of cells treated with cyanobacterial phycoerythrin indicated a dosedependent impact on cell viability wherein, higher dose (200 g/mL) was most potent and accounted for maximum cell growth inhibition (>80%). Transmembrane potential of mitochondria is an important parameter to assess mitochondrial function and overall health of cell Gajaria et al, 2015). In the present study, a dose-dependent decrement in mitochondrial membrane potential was recorded following cyanobacterial phycoerythrin treatment suggesting possible mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 54%
“…Cytotoxicity (MTT) assay of cells treated with cyanobacterial phycoerythrin indicated a dosedependent impact on cell viability wherein, higher dose (200 g/mL) was most potent and accounted for maximum cell growth inhibition (>80%). Transmembrane potential of mitochondria is an important parameter to assess mitochondrial function and overall health of cell Gajaria et al, 2015). In the present study, a dose-dependent decrement in mitochondrial membrane potential was recorded following cyanobacterial phycoerythrin treatment suggesting possible mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 54%
“…Gajaria et al demonstrated the protective effect of curry leaves against the in-vitro LDL-C oxidation and oxidized LDL-Cinduced apoptosis in macrophages due to the antioxidant potentials of flavonoids. 30 Birari et al reported the potent antilipase activity of curry leaves which might be involved in the decreased digestion and thus the absorption of lipids from intestine. 31 Decreased absorption of cholesterol found to increase the LDL receptor on cell surface to uptake the LDL which will lead to decrease blood cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…( Sánchez-Moreno et al .,2002)for example Ohmori et al, 2005),use green tea, ( Thounaojam et al .,2011). use Sida rhomboidea, (Gajaria et al, 2015 andAhmed et al, 2015) use two mint types. Our study we use NS and SL was used for inhibition of LDL oxidation in vitro, the antioxidant activity of both herbals was determined with the ability to remove free radical DPPH and with the ability to remove the reactive oxygen species (superoxide anion O2-), the EO of both herbals possess high ability to inhibit the free radical of DPPH, this finding agreed with (Hajlaoui et al,2009 andAhmed et al, 2015).…”
Section: Discussionmentioning
confidence: 99%